Explosive welding of Al alloys and high strength duplex stainless steel by controlling energetic conditions. (October 2020) - Chen, Xiang; Inao, Daisuke; Tanaka, Shigeru; Mori, Akihisa; Li, Xiaojie; Hokamoto, Kazuyuki
Abstract: In this study, Al alloys and high strength duplex stainless steel plates were welded using explosive welding technology. Compared with the direct welding method, the use of an interlayer can reduce kinetic energy dissipated during the welding of dissimilar metals, which reduce the thickness of excessive melting layer to achieve high-quality welding. Different interface morphologies were observed under different welding parameters. In particular, a flat welding interface was observed which differed from conventional explosive welding, when the velocity of the flyer plate was relatively less. The tensile shear tests and bending tests demonstrated that the welding strength was high when high-quality welding was achieved. The smoothed particle hydrodynamics (SPH) numerical model was used to simulate the welding process, and the simulated interface morphologies were consistent with the experimental results. The jet velocity, temperature, and strain near the interface and the velocity and collision angle of the interlayer at the collision point were calculated using the numerical simulations. As per the discussion based on the weldability window, the difficulty of achieving direct welding between Al alloys and duplex stainless steel was demonstrated. Using weldability window to analysis tri-metallic joints, the analysis revealed why using an interlayer can make the welding easily. Further, a method to realize interlayer welding is presented.